Cardiovascular effects of coumarins besides their antioxidant activity - Najmanová, Iveta; Doseděl, Martin; Hrdina, Radomír; Anzenbacher, Pavel; Filipský, Tomáš; Říha, Michal; Mladěnka, Přemysl (Current topics in medicinal chemistry, 2015)
Coumarins are a large group of substances, primarily of plant origin. Like their more intensively examined congeners flavonoids, many of them are antioxidants. Although such properties may be advantageous in cardiovascular diseases, it has been shown that coumarins exhibit direct effects on the cardiovascular system which are not based on antioxidant activity. The most common example is the well-known drug warfarin, a synthetic compound derived from natural dicoumarol. Moreover, other coumarins have been shown to possess antiplatelet and vasodilatory potential. Interestingly, the former effect may be mediated by the inhibition of various pathways leading to platelet aggregation, their differing effects on those pathways being due to structural differences between the various coumarins. Conversely, their vasodilatory potential is linked in the majority of cases to the inhibition of increases in intracellular calcium concentration in vascular smooth muscle cells, and in several coumarins also to NO-mediated vasodilatation. Available data on both activities are summarized in this review. At the end of this review, relevant data are provided from a few studies testing the in vivo effects of coumarins on major cardiovascular diseases; the clinical use of warfarin and other coumarin anticoagulants, as well as the limited data on the clinical use of coumarins in chronic venous insufficiency and the possible toxicological effects of coumarins.
Keywords: inhibitory agregace trombocytů; antioxidancia; klinické zkoušky jako téma; molekulární struktura; Molecular Structure; vazodilatancia; Coumarins; Vasodilator Agents; kardiovaskulární nemoci; Animals; lidé; objevování léků; Antioxidants; Humans; zvířata; Drug Discovery; Cardiovascular Diseases; kumariny; Platelet Aggregation Inhibitors; Clinical Trials as Topic